Mandibular First Molar with 5 Canals- A Rare Case Report - Shubham, Snigdha; Gautam, Vanita; Singh, Ourvind Jeet (Journal of Universal College of Medical Sciences, 2015)
Success of endodontic treatment is solely dependent upon cleaning and shaping followed by three dimensional obturation. But this is not possible until and unless clinician doesn't have proper knowledge of anatomic variations and complexities. The purpose of this case report is to show the possibility of five root canals in first mandibular molar and imply the importance of scrutiny for identification and treatment of all the canals.